Exposure of the extracellular matrix and colonization of the ovary in metastasis of fallopian-tube-derived cancer. (23rd November 2018) - Dean, Matthew; Jin, Vivian; Russo, Angela; Lantvit, Daniel D; Burdette, Joanna E
Abstract : Ovarian cancer can originate in the fallopian tube. We show that ovarian colonization, exposure of the ovarian extra-cellular matrix as would occur during ovulation, and loss of PTEN in the fallopian tube are important for spread of this disease. Abstract: High-grade serous ovarian cancer (HGSOC) can originate in the fallopian tube epithelium (FTE), but the role of the ovary in these tumors is unclear. Tumorigenic murine oviductal epithelial (MOE) cells allografted in the ovarian bursa resulted in aggressive tumors that spread throughout the peritoneum whereas intraperitoneal xenografting the same number of cells did not form tumors, indicating that colonization of the ovary may play a role in metastasis. Physical tearing of the ovarian surface to mimic rupture of the ovary during ovulation (independent of hormonal changes) resulted in more MOE and HGSOC cells adhering to the ovary compared with intact ovaries. More MOE cells also adhered to three-dimensional (3D) collagen and primary ovarian stromal cells than to ovarian surface epithelia, indicating that FTE cells adhered to the extracellular matrix exposed during ovulation. However, plating cells on 3D collagen reduced the viability of normal FTE but not cancer cells. Mutation of p53 (R273H or R248W) and activation of Kirsten Rat Sarcoma Viral Oncogene Homolog (KRAS) (G12V) did not increase the viability of MOE cells on 3D collagen. In contrast, loss of phosphatase and tensin homolog (PTEN) allowed MOE cells to retain normal viability on 3D collagen. Loss of PTEN activated AKT and RAC1/c-jun N-terminal kinase signaling that each contributed to the increased viability, invasion and attachment in the collagen rich ovarian microenvironment. These results show that loss of PTEN activates multiple pathways that together enhance colonization of the ovary due to access to 3D collagen, which is a critical organ in the colonization of FTE-derived HGSOC.